Buffering Adaptive Immunity by Hydrogen Sulfide - Giulia Pozzi; Giuliana Gobbi; Elena Masselli; Cecilia Carubbi; Valentina Presta; Luca Ambrosini; Marco Vitale; Prisco Mirandola (Cells, 2022)
T cell-mediated adaptive immunity is designed to respond to non-self antigens and pathogens through the activation and proliferation of various T cell populations. T helper 1 (Th1), Th2, Th17 and Treg cells finely orchestrate cellular responses through a plethora of paracrine and autocrine stimuli that include cytokines, autacoids, and hormones. Hydrogen sulfide (H2S) is one of these mediators able to induce/inhibit immunological responses, playing a role in inflammatory and autoimmune diseases, neurological disorders, asthma, acute pancreatitis, and sepsis. Both endogenous and exogenous H2S modulate numerous important cell signaling pathways. In monocytes, polymorphonuclear, and T cells H2S impacts on activation, survival, proliferation, polarization, adhesion pathways, and modulates cytokine production and sensitivity to chemokines. Here, we offer a comprehensive review on the role of H2S as a natural buffer able to maintain over time a functional balance between Th1, Th2, Th17 and Treg immunological responses.